The protein interacting with C-kinase (PICK1) interacts with and attenuates parkin-associated endothelial-like (PAEL) receptor-mediated cell deat - Dev, Kumlesh; O'Connell, Kara (My University, 2014)
The parkin-associated endothelial-like receptor (PAELR, GPR37) is an orphan G protein-coupled receptor that interacts with and is degraded by parkin-mediated ubiquitination. Mutations in parkin are thought to result in PAELR accumulation and increase neuronal cell death in Parkinson's disease. In this study, we find that the protein interacting with C-kinase (PICK1) interacts with PAELR. Specifically, the Postsynaptic density protein-95/Discs large/ZO-1 (PDZ) domain of PICK1 interacted with the last three residues of the c-terminal (ct) located PDZ motif of PAELR. Pull-down assays indicated that recombinant and native PICK1, obtained from heterologous cells and rat brain tissue, respectively, were retained by a glutathione S-transferase fusion of ct-PAELR. Furthermore, coimmunoprecipitation studies isolated a PAELR-PICK1 complex from transiently transfected cells. PICK1 interacts with parkin and our data showed that PICK1 reduces PAELR expression levels in transiently transfected heterologous cells compared to a PICK1 mutant that does not interact with PAELR. Finally, PICK1 over-expression in HEK293 cells reduced cell death induced by PAEALR over-expression during rotenone treatment and these effects of PICK1 were attenuated during inhibition of the proteasome. These results suggest a role for PICK1 in preventing PAELR-induced cell toxicity.
PUBLISHED
Keywords: GPR37